Sustainable product development of biomass briquette from Samanea saman leaf waste with rejected papaya as the binding agent in Indonesia. Issue 1 (1st September 2022) - Hilario, Yusuf; Sahputra, Iwan Halim; Tanoto, Yusak; Jeremy Gotama, Gabriel; Billy, Alexander; Anggono, Willyanto
Abstract: The depletion of solid fuels in the world triggers the requirement for the existence of an alternative fuel product as a substitute. In several studies, briquettes have become one of the alternatives used to deal with this problem. However, the selection of briquette material that considers its impact on economic, social, and environmental aspects has not been widely carried out. To solve this problem, the selection of raw materials for briquettes must be determined using the concept of sustainable product development (SPD). SPD is a concept that can be used to determine a new product by considering various aspects, including economic, environmental, and social aspects. Briquette fuel that is derived from leaf waste and rejected fruit as a binding agent can be an alternative to renewable solid fuels since the raw materials come from wastes that have no selling value. The methodology used in this research is by conducting a survey at five markets in Surabaya and proceeding with interviews with the local government official. Pugh Matrix Concept Selection (PMCS) method is used to determine the suitable raw materials and to analyze the sustainability of the product development. Through PMCS, the results show that the best material for briquette production based on economic, social, and environmental aspects is a mixture of Samanea saman leaf waste with a 12.83 rating value and rejected papaya as the binding agent with a 10.44 rating value. Briquette with a mixture of 95% Samanea saman leaf waste and 5% rejected papaya is produced with a mesh size of 60 or 250 μm and a compression pressure of 2 MPa and is identified to have a heating value of 4025.87 Kcal/Kg.